HIGHLY RELATIVISTIC CIRCULAR ORBITS OF SPINNING PARTICLE IN THE SCHWARZSCHILD AND KERR FIELDS - Plyatsko, R. M.; Fenyk, M. T. (Одеські астрономічні публікації, 2012)
The solutions of the Mathisson- Papapetrou equations which describe highly relativistic circular orbits of a spinning particle in Schwarzschild’s and Kerr’s fields are considered. The domain of existence of those orbits and the necessary values of the particle’s velocity for their realization are studied. These results can be applied while analyzing the synchrotron radiation in some astrophysical processes.